DEPOSITION OF YTTRIA-STABILIZED ZIRCONIA CERAMIC ON SS316L BY PULSED SOLID-STATE ND:YAG LASER - Mardiyanto Mangun Panitra; Abu Khalid Rivai (Jurnal Sains Materi Indonesia, 2019)
Austenitic stainless steel in general has a limited service temperature up to 600°C. Nevertheless, service temperature more than that temperature are one of the key feature of advanced nuclear reactors to gain higher thermal efficiency which is related to economic beneficial, and also to withstand from abnormal condition. However, austenitic stainless steel such as SS316 class is well-known structure material for nuclear power reactors and other power plants. Therefore, one of the key issue is to modify SS316 so that has capability to service higher temperature. One of the technique for that purpose is ceramic-coated SS316L. In this preliminary study, thin films of zirconia-based ceramic i.e. YSZ (Yttria-Stabilized Zirconia) have been deposited on a SS316L using Plasma-Pulsed Laser Deposition (PLD) at Center For Science and Technology of Advanced Materials laboratory – National Nuclear Energy Agency of Indonesia (BATAN). Thin film was deposited with the constant oxygen flow injection of 20 and 40 sccm (Standard Cubic Centimeters per Minute) that produce a chamber pressure of 60 and 200 mTorr for the numbers of laser shots of 7.2×104 and 14.4×104, respectively. The substrate temperature during deposition was of 850oC. Afterward, the samples were analyzed using Optical Microscope, Scanning Electron Microscope – Energy Dispersive X-ray Spectroscope (SEM-EDS) and Atomic Force Microscope (AFM). The results showed that the YSZ could homogeneously and sticky deposited on the surface of the SS316L surface.  The surfaces were very smoothly formed with the surface roughness in the nano-meter scale range of 20-90 nm.